Polaridad en redes sociales y principales indicadores financieros del sector asegurador (2017)
This article aims to show the construction of a comparative management analysis tool, which control the insurance companies through a control panel analyze the behavior of financial management indicators and market opinion on the data Companies The article is based on the information of 25 companies that participate actively in Facebook on Twitter and are affiliated to Fasecolda (Federation of Colombian Insurers). It also shows the utility of using free tools to convert data into information and information into knowledge.